PENDAMPINGAN UMKM ANEKA KRIPIK MELALUI PEMBUATAN LOGO DAN PENGGUNAAN MEDIA ONLINE - Wasito Wasito (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
One form of Tri Dharma education is community service, which has the purpose of providing insight, skills to become an expertise. The underlying thing to do this pendampngan because local residents are less able to utilize information technology, the problems that exist when sales are less than the target, minimal buyers, the target of this community assistance to the villagers sawahan Puncu and surrounding areas. Logo creation assistance in addition to having a purpose as an initial characteristic when viewing a product through packaging, then make it easier for consumers to provide goods of interest. intended to make it easier for consumers to recognize the products sold. To make an appeal to the public, each logo in a product is considered as an initial representation in recognizing the product. has its own distinctive features. Instagram Facebook, Facebook, tokopedia, shopee, in order to make it easier for manufacturers to sell a product, of course by utilizing appropriate technology, such as using social media instagram, facebook, whatasApp business, marketplace. Marketing using online media makes it easier for MSME actors to reach consumers. Many consumers who appreciate which used to be offline, can now serve orders using online applications. And also payment models are already serving with interbank transfers.